Pédagogie Active Et Développement Des Compétences Entrepreneuriales Des Étudiants : Analyse Empirique - Radi, Said (European Scientific Journal, ESJ, 2017)
In order to enable the Moroccan University to provide the country with human resources capable of contributing to its development, a reform of higher education was implemented as from 2003. This reform focuses much more on the development of students’ skills than on the acquisition of knowledge. In this context, the UM5R has set up a Specialized Master in Entrepreneurship and Project Management. The main innovation of this training is the introduction of active pedagogy through two activities: entrepreneurial missions and creativity workshops. This article attempts to answer the question of the extent to which the introduction of this educational innovation has improved the entrepreneurial skills of the students. The chosen research methodology is action research. The main result is that the introduction of active pedagogy has enabled students to effectively develop entrepreneurial skills, to file patents and to create their own companies.